El capital humano como factor de productividad en el sector manufacturero del Ecuador, periodo 2000 - 2021. - Samaniego Jácome, Alex Daniel (2023)
This work analyzes human capital as a factor of productivity in the manufacturing sector of Ecuador during the period 2000 - 2021, determining the incidence that human capital has on productivity in the manufacturing sector, contributing theories that allow us to have a vision of how they relate. It is interesting to measure productivity based on human capital, determining the impact that it can generate in small and large companies in the different economic sectors that the country has. In addition to this, in the present work, the human capital is analyzed through the schooling rate and the investment that the government has in science and technology, where the significance of each variable will be established, through the Generalized Least Squares method (GLS), since it is an amplification of the Ordinary Least Squares (OLS) method.